2007
DOI: 10.1590/s1516-89132007000700013
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of gonads, maturity and spawning season of Loricariichthys spixii (Siluriformes, Loricariidae) in a Subtropical Reservoir

Abstract: The gonad morphology and spawning season of Loricariichthys spixii in Lajes reservoir

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
7
15
0
2
Order By: Relevance
“…The values for GSI also began to rise in August/September, peaking in October/November for females and August/September for males. Similar results were found in other Loricariidae in various regions of Brazil, for example, Rhinelepis aspera (Agostinho et al, 1990), Hypostomus commersonii (Agostinho et al, 1991), H. ancistroides (Viana et al, 2008), Rineloricaria latirostris (Barbieri, 1994), Loricariichthys platymetopon (Bailly et al, 2011;Marcucci et al, 2005), L. spixii (Duarte et al, 2007), among others. Males showed distinctly greater condition factor than that of females throughout the study period, probably because of higher energy expenditure of females during the maturation process (Cantanhêde et al, 2007), a feature also reported by Agostinho et al (1990) for Rhinelepis aspera in the rio Paranapanema (state of Paraná).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The values for GSI also began to rise in August/September, peaking in October/November for females and August/September for males. Similar results were found in other Loricariidae in various regions of Brazil, for example, Rhinelepis aspera (Agostinho et al, 1990), Hypostomus commersonii (Agostinho et al, 1991), H. ancistroides (Viana et al, 2008), Rineloricaria latirostris (Barbieri, 1994), Loricariichthys platymetopon (Bailly et al, 2011;Marcucci et al, 2005), L. spixii (Duarte et al, 2007), among others. Males showed distinctly greater condition factor than that of females throughout the study period, probably because of higher energy expenditure of females during the maturation process (Cantanhêde et al, 2007), a feature also reported by Agostinho et al (1990) for Rhinelepis aspera in the rio Paranapanema (state of Paraná).…”
Section: Discussionsupporting
confidence: 80%
“…In other studies with species of the genus Loricariichthys, e.g. L. platymetopon in the Paranapanema and the Paraná rivers (Marcucci et al, 2005;Bailly et al, 2011) and L. spixii in the Lajes reservoir (Duarte et al, 2007) this pattern also were observed. Although registered for some species, the 1:1 ratio is seldom found.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…During the reproductive period, the species features an accentuated sexual dimorphism characterized by increase of the lip structures formed in the ventral area of males, where eggs remain attached (Dei Tós et al 1997). This type of parental care appears to be common among Loricariidae (Py-Daniel & Cox Fernandes 2005), and has been recorded for L. typus (Machado-Allison & Lopes-Rojas 1975, Machado-Allison 1990, L. anus (Bruschi-Júnior et al 1997) and L. apixii (Duarte et al 2007). For Megalancystrus aculeatus and Hypostomus ternetzi, males guard the nests where the adhesive eggs are laid (Suzuki et al 2000).…”
Section: P T E Ro D O Ra S G Ra N U L O S U S Pa Ra U Ch E N I P T mentioning
confidence: 73%
“…For many Neotropical fish species, the reproductive period is associated with changes in water level (Duarte et al, 2007), which is considered one of the most important seasonal events in freshwater environments (Lowe-McConnell, 1999), along with temperature (Baumgartner et al, 2008). Lower temperature and a high water level seem to influence the gonadal development of both L. grossidens and P. platana in Peri Lagoon.…”
Section: Discussionmentioning
confidence: 99%